PERAN LITERASI DIGITAL ORANG TUA DALAM PENGASUHAN ANAK DI ERA TEKNOLOGI - Zahro Aulia; Suyadi, Suyadi; Rohinah, Rohinah; Melati Puspitajati Adikusuma; Muhammad Khairuman Wahhada; Khoirotin, Khoirotin (Fakultas Tarbiyah Universitas Ibrahimy Situbondo, 2026)
This study aims to analyze the role of parental digital literacy in early childhood parenting in the technology era through systematic literature review, focusing on family psychology in Indonesia from 2019-2025. The PRISMA-guided method screened 97 articles from Google Scholar, Connected Paper, and Scispace using Braun & Clarke thematic analysis with 0.92 interrater reliability. Findings reveal parental digital literacy encompassing technological knowledge, risk awareness, and content supervision dominates adaptive parenting, reducing negative exposure by up to 70%, and supports children's cognitive-emotional development via hybrid conventional-digital approaches rooted in Islam. Key challenges include urban-rural digital divide and socio economic gaps, while benefits strengthen family bonds and resilience against technological disruptions.